Diagnosis of the sustainability level in UNESCO Araripe Geopark’s community - Duarte, Ana Karine Gomes (2021)
Sustainability practices are becoming increasingly imperative to manage any business or quality of life in the global society. This paper addresses this need for change and the United Nations (UN) goals for sustainable development, showing the reality faced by communities via a case study surrounding the UNESCO Araripe Geopark geosites. The study was done to identify points that deserve further visibility to achieve a truly sustainable life. A comprehensive review of the 17 Sustainable Development Goals was carried out. The goals that best adapted to the studied region were chosen, and structured interviews were conducted within the community to obtain an accurate and authentic diagnosis, directed to the strong and weak points of the geosites. This approach allowed for a thorough understanding of the possibilities and threats to incorporating suitable sustainable practices tailored to the studied region's reality.